Emotional regulation in University students (Journal of the College of Basic Education, 2022)
This research aims at:1-Identifying the emotional regulation in university students.,2-Recognizing the emotional regulation in university students according to certain strategies.3- Identifying the statistical significance of emotional regulation based on the following variables A-Gender (Male-Female) B- specialization and field (Pure science, Humanities) C- The Grade (First, Second , Third or Fourth grade) ,4- Recognizing the significance of statistical differences in the level of strategies of emotional regulation based on the following variables:A-Gender (Male-Female) B- specialization and field (Pure science, Humanities) C- The Grade (First, Second , Third or Fourth grades).In order to achieve the research aims, the researcher used the descriptive approach. The research community was selected on the basis of the following sample: students of Baghdad university for the academic year 2014-2015 in colleges of pure sciences and human sciences for full time studies in (1st, 2nd , 3rd and 4th ) grades. The sample includes the students of both (24 ) colleges of human sciences and (12) colleges of pure sciences. The research sample was consisted of 400 male and female students from colleges of Baghdad University for full time studies. The research sample was selected randomly and consisted of 200 male students and 200 female students from both colleges of pure sciences and colleges of human sciences.Scale of Emotional Regulation The scale of emotional regulation was adopted in English Language and then was translated by the researcher. Furthermore, the Psychometric features were verified through the translation validity, apparent and constructive reliability and discriminative power. The consistency principle was verified through the test and retest, as the correlation coefficient reaches to (0,80) and the reliability reaches to (0,83) by following Cronbach's alpha statistic tool and therefore the measurement scale was consisted of 54 items .Through this research, it is concluded that:- University students have good level of emotional regulation.There are no significant statistical differences in emotional regulation in terms of (sex, field and specialization and the grade).In the light of the research outcomes, the researcher concluded the following:It is concluded that the university should set up a training programs on utilizing strategies of emotional regulation for various groups of community and to all age groups for its significance in achieving the psychological adjustment and mental health